Pentoxifylline protects against loss of function and renal interstitial fibrosis in chronic experimental partial ureteral obstruction. Issue 4 (December 2018) - Ma, Hongbao; Lee, Steven; Yang, Yan; Bedi, Puneet; Chou, Shyan-Yih
Abstract: Tubulointerstitial fibrosis (TIF) is a hallmark of chronic kidney disease resulting from diverse etiologies and predicts severity and progression of the kidney disease. To investigate the pathogenesis of TIF, complete unilateral ureteral obstruction (UUO) is the most widely used animal model. However, UUO precludes evaluation of renal function. In the present study, we created a rat model of chronic partial ureteral obstruction (PUO), which allowed assessment of renal function at different intervals after obstruction. We examined the effects of pentoxifylline (PTF), a phosphodiesterase inhibitor used clinically to treat peripheral artery disease, on renal function and TIF. Studies were performed in sham-PUO rats and rats with 14-day PUO or 30-day PUO receiving vehicle in drinking water or PTF (400 mg/liter in drinking water). At day-14 PUO, glomerular filtration rate (GFR) was markedly and similarly depressed in rats receiving vehicle or PTF as compared with sham-operated rats. However, at day-30 PUO, GFR in rats receiving PTF was significantly higher than that in rats receiving vehicle, approaching the level seen in the sham-operated rats. At day-30 PUO, histologic studies also revealed a marked reduction of TIF in rats treated with PTF as compared with the rats receiving vehicle in drinking water. Western blot analysis demonstrated that at day-30 the expression of α-smooth muscle actin (an indicator of renal fibrosis) in the medulla was significantly reduced in PUO rats treated with PTF. In conclusion, PTF treatment ameliorated renal fibrosis and helped preserve renal function in a rodent model of PUO.